Error Analysis in Mother Tongue (Bima Language) Interference In Writing Skill - Diha, Hamjah (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2022)
The objectives of the study are to describe the types of error made by the students in third semester students of STKIP Taman Siswa Bima in academic year 2011-2012, what are the dominances of error and what are the pedagogical consequence in language teaching of writing skill. The method used by the writer in this thesis is case study. The writer used case study because the writer observes activities by students of STKIP Taman Siswa Bima when they conducted the teaching-learning process. In this study, the researcher does not take all of students of STKIP Taman Siswa Bima but the researcher only takes the students of STKIP Taman Siswa Bima especially English department at the third semester in academic year 2011-2012. The techniques of collecting the data are observation, interview, record and transcription. The data collected in this research are the form recording and transcription of students conversation conducted by the students’ and lecturer, and students’ and other. The processes in data analysis are reduction of data, discussion of findings, and conclusion. The results of this study show three types of error made by the students’ of STKIP Taman Siswa Bima at third semester in academic year 2011-2012, it is contains morphological level, lexical level and syntax level. Morphological level consists of omit of prefix -un, omit of suffix -d or -ed, -s or es and omit of -ly. Lexical level contains of verbs, articles, pronouns, adverbs, noun, and conjunction. And syntactical level include of tenses and To Be. In this level, the students omit of To Be in the sentence.